2022
DOI: 10.3390/ijerph19106219
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Predict the Length of Stay of Patients Undergoing Hip-Replacement Surgery?

Abstract: The proximal fracture of the femur and hip is the most common reason for hospitalization in orthopedic departments. In Italy, 115,989 hip-replacement surgeries were performed in 2019, showing the economic relevance of studying this type of procedure. This study analyzed the data relating to patients who underwent hip-replacement surgery in the years 2010–2020 at the “San Giovanni di Dio e Ruggi d’Aragona” University Hospital of Salerno. The multiple linear regression (MLR) model and regression and classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Our model was also well calibrated during internal validation (optimism of −0.002, range −0.300-0.296). Compared to other predictive models, our model has a higher accuracy than the multiple linear regression model from Trunfio et al which achieved an overall accuracy of between 0.651 and 0.718 (20) and is comparable to the model by Knoll et al which had an accuracy of within 3 days of the true LOS for 0.758 of their series (19). There are numerous variations among predictive models in terms of inclusion criteria, candidate predictors and type of regression model that could potentially affect the accuracy of each model (19,20).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our model was also well calibrated during internal validation (optimism of −0.002, range −0.300-0.296). Compared to other predictive models, our model has a higher accuracy than the multiple linear regression model from Trunfio et al which achieved an overall accuracy of between 0.651 and 0.718 (20) and is comparable to the model by Knoll et al which had an accuracy of within 3 days of the true LOS for 0.758 of their series (19). There are numerous variations among predictive models in terms of inclusion criteria, candidate predictors and type of regression model that could potentially affect the accuracy of each model (19,20).…”
Section: Discussionmentioning
confidence: 72%
“…Various predictors for LOS in osteoporotic hip fractures have been reported including delay in time to surgery, previous hip fractures, cerebrovascular disease, smoking status, ASA classification, age and degree of decline in cognitive function (12)(13)(14)(15)(16)(17). Some models to predict LOS in osteoporotic hip fracture patients have been proposed (18)(19)(20). One study created a model to predict LOS in hip fractures (both intertrochanteric and femoral neck types) (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work showed that infection control programs with dedicated hospital epidemiologists and surveillance programs reduced nosocomial infections by 32% compared to facilities without infection control programs [ 8 ]. To design an effective prevention program, it is necessary to consider the impact that SSIs have on the length of hospital stay [ 9 , 10 , 11 , 12 ], which is a performance indicator of the quality of health processes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In addition, identifying risk factors associated with SSIs can help reduce the incidence of SSIs [ 11 , 20 ] and add value to HTA studies, which are widely used to support health decision-making [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports that the evaluation of LOS through advanced analytical techniques and artificial intelligence algorithms is the subject of numerous studies [ 8 , 9 , 10 , 11 , 12 ]. History has verified that some populations with high-grade carotid stenosis are at high risk of subsequent stroke [ 13 ].…”
Section: Introductionmentioning
confidence: 99%